Palaeogeographic and palaeoclimatic evolution of the Po Plain from 150-ky core records - Amorosi, A; Colalongo, M.L; Fiorini, F; Fusco, F; Pasini, G; Vaiani, S.C; Sarti, G (Global and planetary change, 2004)
Integrated sedimentological and micropalaeontological (foraminifers, ostracods, pollen) analyses of eight continuously cored boreholes, up to 140 m deep, reveal the depositional history and the palaeoclimatic evolution of southeastern Po Plain (northern Italy) over the last 150 ky. Age assignments are supported by the chronostratigraphic sequence framework calibrated by radiocarbon and pollen data, allowing detailed correlation with the oxygen-isotope record. Facies analysis (including identification of 12 distinct microfossils associations) and detailed stratigraphic correlations across several tens of km document a cyclic sedimentation pattern (including continental, coastal and shallow-marine deposits), which defines two transgressive–regressive sequences, deposited over the last two interglacial–glacial cycles. Two prominent stratigraphic markers, corresponding to wedge-shaped coastal sand bodies, are recorded between 0–30 and 100–125 m core depths. These sedimentary bodies were deposited during the two major transgressive pulsations and subsequent sea-level highstands of the last 150 ky, assigned to the Holocene and the Tyrrhenian (oxygen-isotope Substage 5e), respectively. The stratigraphic architecture of post-Substage 5e deposits shows consistent patterns of coastal evolution with changing sea-level position. Lowering of sea level between 125 and 70 ky (onset of Substages 5d and 5b, and Stage 4) resulted in extensive and repeated basinward shifts of facies, which can be observed across closely spaced unconformity surfaces associated to alluvial plain sedimentation (falling-stage systems tract). The general phase of sea-level fall was punctuated by short transgressive phases (Substages 5c, 5a and Stage 3 interstadials), which led to widespread deposition of organic-rich (lagoonal and swamp) deposits. Upper Stage 3 and Stage 2 deposits (lowstand systems tract) are replaced across a significant part of the study area by a hiatal surface. Holocene interglacial deposits are characterized by a retrogradational stacking pattern of coastal plain and littoral facies (transgressive systems tract), reflecting invariably the landward migration of a barrier–lagoon–estuary system. Subsequent highstand deposition (highstand systems tract) was characterized by extensive progradation of wave-influenced deltas and strandplains. The two major transgressive surfaces, of Tyrrhenian and Holocene age, are considerably easier to identify than the other key surfaces for sequence stratigraphic interpretation. The lowermost transgressive deposits display a pollen signature diagnostic of warm climate (interglacial) periods, showing wide forest development and relatively high pollen concentrations. By contrast, the deposits overlying the unconformable surfaces related to successive phases of sea-level fall are fingerprinted by pollen spectra dominated by Pinus and non-arboreal pollen types, with very low pollen concentrations, reflecting the onset of a stable cold climate vegetation characteristic of stadial to fully glacial conditions. The good match between facies architecture, pollen distribution and global sea-level evolution strongly suggests that Late Quaternary sedimentation in the Po Basin developed under a predominantly glacio-eustatic control. Stratigraphic architecture of the Po Basin thus can provide a useful analog for interpretation and correlation in the stratigraphic record of very rapid glacio-eustatic (fourth-order) cycles, with frequencies of about 100 ky.